Russula rajmahalensis: A New Species of Russula (Russulaceae, Russulales) from Jharkhand State, India - , Aniket Ghosh; , Manoj Emanuel Hembrom; , Kanad Das; , Dyutiparna Chakraborty (Archives of Current Research International, 2025)
One new species of Russula, namely R. rajmahalensis belonging to subg. Heterophyllidiae sect. Ingratae is proposed herein based on its morphological features and nrITS-based phylogenetic inference. Russula rajmahalensis is characterized by pale yellow, light yellow to light orange pileus centrally with brown to dark brown; subdistant to close, adnexed, yellowish white lamellae; chalky white to yellowish white stipe with rusty brownish spots at the base; hymenial cystidia subcylindrical, subclavate to clavate with rounded, capitate, subcapitate or appendiculate apex; basidiopores subglobose to broadly ellipsoid, composed of amyloid obtuse warts, locally subreticulate, rarely isolated, fused in pairs or short chains, connected by occasional, fine, long line connections and occurrence under Shorea robusta. A detailed descriptions accompanied with colour photographs of the basidiomata, nrITS-based molecular phylogeny and comprehensive comparisons with similar species are also provided.